1999
DOI: 10.1097/00005131-199909000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Design for Fixation Implants on Local Infection: Experimental Study of Dynamic Compression Plates versus Point Contact Fixators in Rabbits

Abstract: After local bacterial challenge, we found a statistically significant difference in the infection rates depending on the implant design. The higher infection resistance associated with the PC-Fix design seems to be related to the reduced contact area at the bone-implant interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 30 publications
1
40
0
4
Order By: Relevance
“…However, we assumed that the effect of bFGF administration would be at least as significant as the effects of various osteosynthesis materials on local infection resistance. In previous investigations with the same experimental design, approximating to 1 ID50 and incorporating the previously mentioned parameters, an infection rate for the titanium dynamic compression plate of 35% had been demonstrated in contrast to 75% for the steel DCP (Arens et al 1996). In keeping with these values, we assumed an effect size of 0.4, corresponding to an infection rate of 30% (50-20) for at least one of the groups with bFGF treatment and 70% (50 + 20) for the group without bFGF treatment.…”
Section: Bacterial Inoculummentioning
confidence: 90%
See 1 more Smart Citation
“…However, we assumed that the effect of bFGF administration would be at least as significant as the effects of various osteosynthesis materials on local infection resistance. In previous investigations with the same experimental design, approximating to 1 ID50 and incorporating the previously mentioned parameters, an infection rate for the titanium dynamic compression plate of 35% had been demonstrated in contrast to 75% for the steel DCP (Arens et al 1996). In keeping with these values, we assumed an effect size of 0.4, corresponding to an infection rate of 30% (50-20) for at least one of the groups with bFGF treatment and 70% (50 + 20) for the group without bFGF treatment.…”
Section: Bacterial Inoculummentioning
confidence: 90%
“…We applied a grouped sequential experimental procedure with an "up-and-down" dosage technique. As described in previous publications, this technique allows the determination of the level of bacterial concentrations at which differences in the infection rates of the groups being compared are most evident (Melcher et al 1994, Hauke et al 1996, Arens et al 1996, 1999a, b, Kälicke et al 2003. This concentration is close to the level of the infection dose of 50% (ID 50 ) (Reed and Münch 1938).…”
Section: Bacterial Inoculummentioning
confidence: 99%
“…Biomechanical and histological testing by many investigators has shown the superiority of point contact fixator (PC-Fix) over standard and limited contact DCP in the management of fractures [1,3,7,9,17]. Plates with nuts on the undersurface that lock the screws into the holes behave in the same manner as a PC-Fix [6].…”
Section: Discussionmentioning
confidence: 99%
“…Plates with nuts on the undersurface that lock the screws into the holes behave in the same manner as a PC-Fix [6]. As the plate is not in contact with the bone, cortical vascular disrup- tion is avoided, leading to better healing potential and possibly a lower infection rate [1]. The implant loses rigidity in its position away from bone, but through the locking nuts maintains adequate stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation